PSYCHOLOGICAL SUPPORT FOR FORMATION OF AN EMPATHY–TOLERANT ATTITUDE OF THE PARENT’S SCHOOL STAFF TOWARDS CHILDREN WITH PSYCHOPHYSICAL DISORDERS - Tzarkova, Olga; Ponomarenko, Victoria (PSYCHOLOGICAL JOURNAL, 2018)
The spread of inclusive education of children with physical and/or mental disabilities in Ukraine is not only a reflection of time, but also a step towards the full realization of the rights of children with mental and physical disabilities to quality education. Such authors as A. Duska, G. Maize, V. Sorokin, V. Tzarkova in their works reveal the psychological problem of parent’s attitude to their children with psychophysical disorders. But in the scientific literature, the question of the psychologist’s tasks with the provision of educational and advisory assistance to the parents’ school staff in the formation of empathic and tolerant attitude to children with psychophysical disorders is covered quite limited. The problem of tolerance and empathy today is one of the central problems of both global and national order. The stability and well-being of the world in the third Millennium depend to a large extent on the ability of people to be tolerant, to respect other cultural and social characteristics, to understand and cooperate, to seek and find solutions to sociocultural conflicts. Empathy allows us to understand the essence of the other. Not so much to understand how to catch the secret movements of his soul: the essence of motives and the meaning of actions, sources of interest or apathy, the causes lie or sincerity of purpose of closed or abandon, etc. The study of the practical state of the problem of inclusion confirmed the urgent need for a special organization of the social environment for the inclusion of children with mental and physical disabilities in joint activities with healthy peers in educational institution. One of the participants of the educational process are the parents of the student group, which form the children’s perception of the world and attitude to other people. Practice shows that the most intensively cooperate those children whose parents have created a favorable psychological climate in the family and serve as an example of goodwill and high moral culture . The purpose of the article is to determine the value and implementation of psychological support of empathic and tolerant attitude of the school parent team to children with psychophysical disorders in secondary school with inclusive education. Based on the understanding of the purpose of the work, we formulate the objectives of the article: 1) to theoretically substantiate the features of the practical psychologist on the formation of empathy-tolerant attitude of parents of the student group to children with psychophysical disorders in ordynary school with inclusive education; 2) clarify the basic concepts of research: empathic attitude, tolerant attitude, psychological support; 3) to conduct its own experimental study to study the features of psychological support of empathic and tolerant attitude of parents of the student group to children with psychophysical disorders in secondary school with inclusive education; 4) to theoretically substantiate effective methods and techniques of forming empatico-tolerant attitude of the parents of the student team for children with mental and physical disabilities. The study, which we conducted with parents in secondary school in an inclusive and regular classes on the following methods: test of communicative tolerance V. Boyko, Express questionnaire “tolerance Index” G. Soldatov, A. Kravtsov, A. Huhlaev, L. Shaigerova, methods of diagnosis of the level of empathic abilities V. Boyko, “scale of emotional response” (BEES). Mehrabyan, N. Epstein, Questionnaire for parents , showed the following results: in a normal class there is no high level of tolerance, unlike in an inclusive class—18%; the level of empathic abilities in percentage value in both classes does not differ; in the normal class “for coeducation of children of both categories” 50%, inclusive 100% of parents. All this makes it possible to conclude that due to the lack of information and stereotypes parents of ordinary children against inclusive education. Psychological support involves purposeful, well-planned work with all categories of participants of the educational process-teachers, students, parents, the public in compliance with the principle of continuity in the main areas: - diagnostic work; - preventive and educational activities; - correction rehabilitation and educational work; - consulting work; - organizational and methodological activities. That is why the main tasks of the practical psychologist in the formation of empathic and tolerant attitude of the school team of parents to children with psychophysical disorders is: the formation of adequate attitudes concerning children; formation of the attitude to the child as to the person with potential; formation of the adoption of the child as it is.